Monetary Transmission through Rural Banks on Economic Development - Mangasa Augustinus Sipahutar; Tarida Marlyn Surya (Universitas Negeri Malang, 2018)
This study aims to measure the role of BPRs in monetary transmission to MSMEs, especially in Municipality and District of Bogor that geographically bordering directly. Determination of these two areas is intended to understand the credit depth of BPRs in relation to regional economic growth, and the results are expected to avoid economic disparity in both regions. This study used VECM model to measure the causality between credit depth and economic growth, and OLS to measure the relationship between poverty to unemployment and credit depth. The VECM model showed uncertainty of Granger's causality between credit depth and economic growth. This explained that it takes higher credit depth of BPRs to promote economic growth. For Municipality of Bogor, changed of credit depth by 1 basis point, reduce poverty by 3.51 basis points, and changed in unemployment by 1 basis point, change poverty in the same direction by 0.09 basis points. Meanwhile, in District of Bogor, changed of credit depth by 1 basis point, reduce poverty by 6.95 basis points, and changed in unemployment by 1 basis point, change poverty in the same direction by 0.26 basis points. Keywords: monetary transmission, MSMEs, rural banks, povertyJEL Classification: E50; G21; R58